System of improvement coacher's professional skill of national teams of Ukraine in Olympic sports - Dutchak M.V; Shkrebtiy J.M; Tomashevskyi V.V (Kharkov National Pedagogical University, 2010)
In the article the condition and prospects of perfection of system of improvement of professional skill of coaches and doctors involved in preparation of sportsmen of Ukraine to Olympic games, the World championships and Europe by summer and winter sports is considered. It is shown that the system of improvement of professional skill should be flexible and mobile with elements of distance learning. The optimal is the multilevel system of improvement of professional skill consisting of three subsystems: self-improvement, participation in the organised forms of improvement of professional skill, analytical and scientifically-practical activities.